Effect of 17a-Methyltestosterone on the growth, survival and sex reversal of Macrobrachium rosenbergii (de Man) - Tan Kim Hooi (Serdang, Selangor: Universiti Pertanian Malaysia, 2012)
Experiments were conducted to determine the potential for promoting growth and controlling sex of Macrobrachium rosenbergii by administration of synthetic androgen, 17a-methyltestosterone(MT). Four experiments were done.